Introducing internet-based cognitive behavioral therapy in the Latvian government-funded mental health sector - Kince-Laus, Ieva; Sile, Liene; Novickis, Jurijs; Romanovska, Elizabete; Dambiņa, Liene; Taube, Maris (Frontiers in Psychiatry, 2025)
As mental health challenges grow globally, innovative interventions are being sought. Internet-based Cognitive Behavioral Therapy (iCBT) offers a promising alternative to traditional psychotherapy—reducing costs, improving accessibility, and addressing healthcare worker shortages in the public sector—essential for Latvia, where many people live in rural areas, have limited income and there is a lack of mental health specialists, making it difficult for patients to access psychological support. In 2024, Latvia launched its first government-funded iCBT pilot. This study introduces the framework and implementation strategy of the Latvian iCBT pilot, done in collaboration with Finland’s HUS and the HealthFox platform. The program targets young adults from the age of 18 to 25 with mild to moderate depression and anxiety, based on validated clinical thresholds (PHQ-9 >8, GAD-7 >10). The population clinical symptoms were designed similarly to previous experience with iCBT evaluated in Finland. The structured therapy, delivered through a mobile app, includes weekly guided sessions, personalized therapist feedback, and interactive digital modules. This article examines the architecture of the pilot—its referral system, therapy modules, data collection process, and therapist responsibilities. Also, it is looking at it within broader global evidence on iCBT efficacy, dropout rates, and patient satisfaction.